On Feeling Warm and Being Warm: Daily Perceptions of Physical Warmth Fluctuate With Interpersonal Warmth. Issue 5 (July 2018) - Fetterman, Adam K.; Wilkowski, Benjamin M.; Robinson, Michael D.
Previous investigations have linked laboratory manipulations of physical warmth to momentary increases in interpersonal warmth. However, replication concerns have occurred in this area, and it is not known whether similar dynamics characterize daily functioning. Two daily diary studies (total N = 235) suggest an affirmative answer. On days in which participants felt physically warmer, they perceived themselves to be interpersonally warmer and more agreeable, irrespective of the outdoor temperature. These findings are consistent with frameworks proposing that people draw on concepts of physical warmth to represent feelings of interpersonal warmth and they highlight the value of using daily diary and within-subject designs to investigate embodied cognition as well as other priming effects.